Teacher talk patterns in classroom interaction in English at a Tamil Primary School / Tisha Nair Balakrishnan - Tisha Nair, Balakrishnan (2018)
Teacher talk is the speech pattern used by teachers in organising and managing their classrooms. Teacher talk is not only a means for teachers to do this as they administer their classes, it is also the major source of comprehensible target language input for L2 acquisition. Therefore, it is an important aspect to focus on in language teaching. This study analyses the patterns of teacher talk in the classroom interactions of two English teaching teachers who were based in one Tamil primary school. The study uses video recording and classroom observation to collect data while teacher talk patterns were classified according to the 13 features proposed by Walsh (2006) in the SETT framework and three other features added by the researcher to suit the classroom discourse used by the teacher participants in this study. Data were transcribed word for word and further verified by the teachers before they were analysed accordingly. The findings showed that the classroom interactions were mainly a one-way classroom interaction where teachers use more referential questions to encourage student talk. Teachers also used interactional modifications during the negotiation of meanings with more extended teacher turns used for modifications. In feedback, teachers applied more form-focused feedback than content feedback. Moreover, the teacher talk patterns differ between both the teacher participants as their teacher talk patterns are influenced by students’ level of proficiency. This study suggests that teachers should exert more extended wait-time and extended learner turn to stimulate student interactions so as to produce more effective comprehensible input and output.